Young Indiana Jones and the tomb of terror - Martin, Les, 1934- (NY: Random House, 1990)
In 1913 in Luxor, Egypt, an ancient ring leads Indy to a hidden tomb and into terrifying adventures with a German archaeologist.
Accelerated Reader AR
Keywords: Adventure stories; Egypt -- Fiction